2015
DOI: 10.15537/smj.2015.8.12204
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic assessment of impacted teeth and associated pathosis prevalence

Abstract: Objectives:To assess the prevalence of both impaction and associated pathosis in a Saudi population in Al-Madinah, Saudi Arabia based on digital panoramic radiographs.Methods:This study was carried out from December 2013 to February 2015. Panoramic radiographs of 359 male patients attending the Oral Diagnosis Clinics, Faculty of Dentistry, Taibah University, Al-Madinah, Saudi Arabia were reviewed. All images were evaluated to determine the prevalence and pattern of impacted third molars and canines, and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 18 publications
7
19
5
Order By: Relevance
“…Researchers have emphasized the importance of the removal or continuous follow-up of impacted maxillary and mandibular third molars because their localized effect on the second molar may result in traumatic/pathological effects or overall remaining dentition [25]. Orthodontic treatment with first premolar extraction can improve third molar angulation during eruption and consequently support the orthodontic extraction therapy approach in borderline cases [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers have emphasized the importance of the removal or continuous follow-up of impacted maxillary and mandibular third molars because their localized effect on the second molar may result in traumatic/pathological effects or overall remaining dentition [25]. Orthodontic treatment with first premolar extraction can improve third molar angulation during eruption and consequently support the orthodontic extraction therapy approach in borderline cases [26].…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontic treatment with first premolar extraction can improve third molar angulation during eruption and consequently support the orthodontic extraction therapy approach in borderline cases [26]. Although the percentage of pathosis associated with impaction is considerably low, regular oral examinations are necessary to preserve asymptomatic impacted third molars in good conditions [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Gashi et al, [21] retrospectively investigated the records of 8101 Kosoviar patients treated in the University Dentistry Clinical Center of Kosovo, The result revealed that the incidence of maxillary canine impaction was (1.62%). A study done in Saudi Arabia assessed the panoramic radiographs of 359 males found that 6 patients had at least one impacted maxillary canine which accounted for 1.67% of the studied population [22]. A prevalence of 1.36% was reported by Mustafa [18] who conducted a retrospective investigation on 3800 panoramic x-rays of patients who had attended for treatment at the faculty of Dentistry at King Khaled University in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%